The effects of resveratrol on ovarian hyperstimulation syndrome in a rat model - Sebnem Ozgur; Mesut Oktem; S. Ozlem Altinkaya; Emel Ozalp Oktem; Cahit Cenksoy; Ozlem Erdem; Sehri Elbeg; Ayse Helvaci; Ahmet Erdem; Mehmet Erdem (Elsevier, 2018)
Objective: The aim of the present study was to investigate effects of resveratrol (RSV) over ovarian hyperstimulation syndrome (OHSS) in rat model. Materials and Methods: 24 female Wistar rats (22 days old) were divided into four groups. Group 1 (control group; n = 6) received 0.1 ml intraperitoneal (IP) saline from days 22-26; group 2 (mild-stimulated group; n = 6) received 10 IU pregnant mare serum gonadotropin (PMSG) on day 24 and 10 IU of hCG 48 h later (day 26); group 3 (OHSS group; n = 6) was given 10 IU of PMSG for 4 consecutive days from day 22 and 30 IU hCG on the fifth day to induce OHSS; group 4 (OHSS + RSV group; n = 6) was treated the same as group 3, but received 60 mg/kg RSV 2 h before PMSG injection for 4 consecutive days and 2 h before the hCG injection on the fifth day. Results: Weight gain was highest in the OHSS group. Ovarian weights were lower in the treatment group than OHSS group. Peritoneal fluid VEGF levels were lower for RSV group compared to group 2 and 3. Total VEGF immunoreactivity was higher in OHSS group than group 1, 2 and 4. Conclusion: These results indicate that RSV is beneficial for prevention of OHSS by reducing the increases in body and ovarian weight and VEGF activity. These effects may be mediated by anti-inflammatory, anti-oxidant and anti-angiogenic capacity of RSV.